2011
DOI: 10.1002/tox.20610
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fe and Ag nanoparticles on seed germination and differences in bioavailability during exposure in aqueous suspension and soil

Abstract: The potential environmental toxicity of zero-valent iron nanoparticles (nZVI) and three types of nanosilver differing in average particle size from 1 to 20 nm was evaluated using seed germination tests with ryegrass, barley, and flax exposed to 0-5000 mg L(-1) nZVI or 0-100 mg L(-1) Ag. For nZVI, germination tests were conducted both in water and in two contrasting soils to test the impact of assumed differences in bioavailability of nanoparticles. Inhibitory effects were observed in aqueous suspensions at 250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
150
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(159 citation statements)
references
References 45 publications
(49 reference statements)
4
150
0
5
Order By: Relevance
“…AgNPs of different sizes, shapes and concentrations affect germination frequency differently. Small-sized NPs exert more inhibitory effects (El-Temsah and Joner 2012). With the passage of time, seed germination frequency was also increased in all (Brunner et al 2006).…”
Section: Effect Of Mnps Suspension On Seed Germinationmentioning
confidence: 93%
“…AgNPs of different sizes, shapes and concentrations affect germination frequency differently. Small-sized NPs exert more inhibitory effects (El-Temsah and Joner 2012). With the passage of time, seed germination frequency was also increased in all (Brunner et al 2006).…”
Section: Effect Of Mnps Suspension On Seed Germinationmentioning
confidence: 93%
“…The studies on soils have revealed that NP-induced toxic effects may significantly decrease with the prolongation of contact time between NPs and the soil (Jośko and Oleszczuk 2013). Furthermore, the existing studies of bottom sediments have been hitherto conducted on one sediment type, whereas the physicochemical properties of the matrix are of key importance for the fate of NPs (among others, their bioavailability and toxicity) (Shoults-Wilson et al 2011;El-Temsah and Joner 2012;Jośko and Oleszczuk 2013). Benthic sediments are characterized by great variation in terms of grain size distribution and chemical properties within one body of water.…”
Section: Introductionmentioning
confidence: 99%
“…At these high levels, overt toxicity is frequently observed. For example, reduced germinated was noted with nanoparticle ZVI on Hordeum vulgare and Linum usitatissimum seeds at 250 mg/L, NP-ZnO on Zea mays seeds at 2000 mg/L, and CeO 2 on Medicago sativa, Zea mays and Cucumis sativus seeds at 2000 mg/L (Lin and Xing, 2007;LopezMoreno et al, 2010b;El-Temsah and Joner, 2012;Feizi et al, 2012;Ghafariyan et al, 2013). Compared to metal-based ENMs, CNTs were shown to not affect seed germination even at 2000 mg/L (Lin and Xing, 2007;Miralles et al, 2012a).…”
Section: General Toxicity Tests On Seeds/seedlingsmentioning
confidence: 99%
“…To date, the knowledge of ENMs-crop interactions in soil-based systems is very limited. In some published trials, sand or soil was either amended with nanomaterial powders or with ENMs suspensions (Du et al, 2011;Dimkpa et al, 2012;El-Temsah and Joner, 2012;Priester et al, 2012;Zhao et al, 2012a;Khodakovskaya et al, 2013). A design with outdoor lysimeters under field condition was first introduced to investigate the impact of ENMs on Triticum aestivum (wheat) growth and soil enzyme activities; here, the topsoil was ex-situ amended with TiO 2 and ZnO nanoparticles (Du et al, 2011).…”
Section: Laboratory Designed Exposure Conditionsmentioning
confidence: 99%